POLEMIK MALPRAKTIK DAN RISIKO MEDIK - Siregar, Rospita Adelina (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
The term negligence is part of professional incompetence, from a health perspective, the term negligence is called malpractice, meaning bad practice, giving rise to claims that go to court. Whereas, medical risks are unexpected events, such as surgery or other medical procedures, which contain medical risks which can actually become an obstacle to medical practice. Society finds it difficult to differentiate between malpractice and medical risk, so it is important to share this knowledge with legal officials and society, so that it does not become a polemic throughout the ages.